2015
DOI: 10.1016/j.bbadis.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for incorporating scientific knowledge and practice on rare diseases into higher education: neuronal ceroid lipofuscinoses as a model disorder

Abstract: This article addresses the educational issues associated with rare diseases (RD) and in particular the Neuronal Ceroid Lipofuscinoses (NCLs, or CLN diseases) in the curricula of Health Sciences and Professional's Training Programs. Our aim is to develop guidelines for improving scientific knowledge and practice in higher education and continuous learning programs. Rare diseases (RD) are collectively common in the general population with 1 in 17 people affected by a RD in their lifetime. Inherited defects in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The study by Cismondi et al (2015) that set out to develop guidelines for improving scientific knowledge about RDs found a situation similar to that shown by this study. When the database in the medical field pub MED was analysed for the period 2005 to 2014 it showed that 12,646 papers on RDs had been published, but when the term medical education was specified the number fell to 377.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The study by Cismondi et al (2015) that set out to develop guidelines for improving scientific knowledge about RDs found a situation similar to that shown by this study. When the database in the medical field pub MED was analysed for the period 2005 to 2014 it showed that 12,646 papers on RDs had been published, but when the term medical education was specified the number fell to 377.…”
Section: Resultssupporting
confidence: 83%
“…Some were related to the training of medical and healthcare staff in the field of RDs (Jinnah, 2011;Van Karnebeek et al, 2012). Others had to do with university studies and knowledge, as in the case -for example -of the paper by Cismondi et al (2015), which addressed the educational issues associated with particular rare diseases in the curricula of Health Sciences and Professional Training Programs. Many others presented a study related to a particular RD, for example that by Chisolm et al (2014) or that by Smith et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…As Cismondi et al rightly observe, “the academic sector lacks initiatives to improve the knowledge of health professionals on complex topics such as RDs” [ 44 ]. The results of this study seem to have largely confirmed the previous findings [ 45 47 ] and suggest that healthcare professionals’ in Poland possess insufficient knowledge on RDs and are unprepared to care for RD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings confirm that nursing curricula contains an insufficient amount of information about rare diseases. Such a suggestion was formulated earlier [20,51], but our research is extended beyond future physicians. What is important is that is shows that there is, on the one hand, the need to expand knowledge, on the otherhigh acceptance of such a solution among the respondents.…”
Section: Discussionmentioning
confidence: 99%